The representation of EFL context-based cultures in an international EYL textbook - Nurhayati, Lusi; Triastuti, Anita; Widodo, Pratomo (Faculty of Languages, Arts, and Culture Universitas Negeri Yogyakarta, 2023)
The present content analysis study intended to investigate the cultural contents of an international EYL textbook used in Indonesian private elementary schools. It examined the representation of cultural themes categorized under the big